The Ambivalent Ageism Scale: Developing and Validating a Scale to Measure Benevolent and Hostile Ageism - Cary, Lindsey A; Chasteen, Alison L; Remedios, Jessica (The Gerontologist, 2017)
Much like sexism, ageism is a multifaceted prejudice; it involves benevolent and hostile attitudes toward older adults. There are many scales designed to measure hostile ageism, yet none dedicated to measuring benevolent ageism. In the current studies, we developed and validated a 13-item measure: the Ambivalent Ageism Scale (AAS). We employed four stages of scale development and validation. In Stage 1, we created 41 benevolent ageist items adapted from existing ageism measures. In Stages 2 and 3, we further refined the pool of items through additional testing and factor analysis and retained nine items loading strongly on two factors related to benevolent ageism: cognitive assistance/physical protection and unwanted help. In order to enable researchers to contrast benevolent and hostile attitudes, we then added four hostile ageist items. In Stage 4, we assessed the test-retest reliability of the 13-item scale. The AAS had good test-retest reliability (r = .80) and good internal consistency (α = .91). As predicted, the benevolent and hostile ageism subscales differentially predicted attitudes toward older adults: higher scores on the hostile subscale predicted lower competence and warmth ratings, whereas higher scores on the benevolent subscale predicted higher warmth perceptions. The AAS is a useful tool for researchers to assess hostile and benevolent ageism. This measure serves as an important first step in designing interventions to reduce the harmful effects of both hostile and benevolent ageism.